Analisis Survival pada Penderita Gagal Ginjal Kronik dengan Komorbiditas Diabetes Melitus - Nova Muhani; Nurhalina Sari (Media Kesehatan Masyarakat Indonesia, 2020)
Chronic Kidney Disease (CKD) is a global public health problem with an increasing prevalence and incidence of kidney failure a poor prognosis and high treatment costs. CKD is the leading cause of death globally, the biggest cause of CKD is comorbidity with diabetes mellitus. the highest mortality occurred in the first 6-12 months undergoing hemodynamic which is 33%. The purpose of this study was to determine the age, sex, hemoglobin level, and survival time of CKD patients undergoing hemodialysis based on diabetes mellitus comorbidity. The study design was a prospective cohort, with a sample of 159 respondents. The study used data from the daily report of the hemodialysis unit Abdul Moeloek Hospital in Lampung Province, responded is new patients undergoing hemodialysis were then observed for 12 months. The analysis used a survival analysis with Cox regression. The results showed an average survival of 5 months, death occurred (event) by 47.8%, patients with CKD with Diabetes mellitus comorbidity 27.7%. Hemodialysis respondents type of female (55,3%) and male (44,7%), age less than 60 years 64.4%, hemoglobin levels less than 7 mg% (severe anemia) 28.4%. Statistical test results obtained sex p=0.602, age p=0.582, anemia p=0.567, and a history of diabetes mellitus (p=0.001 with α=0.05, (Risk Ratio=2.3). CKD Patients with comorbidities with diabetes Mellitus they are should better maintain health with a protein diet and control blood sugar.